Evaluation of the hydric resources in the hydrographic system of Mijares-La Plana. Effects under a scene of climatic change - José Quereda Sala; Enrique Montón Chiva; Belén Mollá Cantavella; María Victoria Quereda Vázquez (Boletín de la Asociación de Geógrafos Españoles)
This work proposes two objectives: responding to the basic issue of how much water there is as well as projecting the water resources in the future. Evaluating evapotranspiration was the main methodological innovation of our work, made by Penman–Monteith method. Kriging techniques have been applied over the values from meteorological observation points to get a regular grid, used to calculate regional average values. Concluding, resources are currently tight to serve the demand, but they may be seriously committed to the changes estimated by climatic models.